Learning Assistance And Capacity Building For Outreach To Volunteers And People With Hiv-Aids Ngo Jakarta Plus Center In Cirebon Indonesia - Erlina Puspitaloka Mahadewi; Mohamad Reza Hilmy; Ade Heryana; Mulyo Wiharto (CV. Inara, 2021)
The present study is for achieve also improving the education and information provided to hiv-aids cadre and patients. The existence of patients with hiv-aids is one of the communities that is difficult to reach, so health cadres and volunteers should have the ability to prevent hiv-aids and related health knowledge, which should be above average. The main and most important task of health cadres and or volunteers is to reach community groups with high health risks, and difficult to find by health workers. This study aims to gradually increase the capacity of health management skills, especially healthcare interpersonal speaking speech for volunteers and health cadres. The research was conducted using the method or approach of capacity building and PRA (Participatory Rapid Appraissal). Mentoring activities that have been carried out for 3 consecutive years in August 2019, September-October 2020, and October 2021 during the covid-19 pandemic. This activity was attended by more than 20 cadres, health volunteers, and administrators from the NGO Jakarta Plus Center (JPC) Foundation, both Jakarta in 2019-2020 and Cirebon in 2021. The training time during capacity building was about 1 hour for each topic, with presentations, simulations and role plays. in field assistance in 2020 and 2021 for a full day. The method of measuring understanding and knowledge is done by pre-test and post-test, before and after the activity. The results of the research show that although there is a statistically significant difference between participants knowledge during the initial test and at the end of the training, the data shows an improvement in participants' knowledge in mentoring and outreach activities. It is necessary to follow up research activities in the following years in the form of research on more detailed field assistance on disaster management, special community communication field education for the empowerment of volunteers and cadres at the JPC Foundation during the pandemic and preparations after it.